(untitled) (Revista Latino-Americana de Enfermagem, 2010)
The aim of this study was to compare the demographic factors and the risk indicators for the occurrence of the stroke in the city of Fortaleza with other cities, based on national studies. A transversal study developed with 180 patients who were diagnosed with stroke in nine different public institutions within the period from October 2007 to April 2008. For data collection, a questionnaire was applied by interviewing the patient and/or their companions. The following tests were used for the comparative analysis of epidemiological data: The Chi-Square Test for the adherence and the T-Test for the mean. The patients with stroke evaluated in Fortaleza were younger and had higher rates of hypertension than in the national profile, however, fewer were smokers or consumers of alcohol. It is necessary to increase knowledge about the health of the Brazilian population by region, since there are specific influential factors in the occurrence of stroke.